Depression symptoms as longitudinal predictors of the psychological impact of COVID-19 pandemic in hypertensive patients - Marco D’Addario (Nature Portfolio, 2021)
Abstract COVID-19 has brought considerable changes and caused critical psychological responses, especially among frail populations. So far, researchers have explored the predictive effect of diverse factors on pandemic-related psychological distress, but none have focused on the impact of prior depression and anxiety symptomatology adopting an extended (10-year) longitudinal design. 105 patients aged over 60, affected by hypertension who participated in a previous longitudinal study were assessed through a follow-up telephone structured interview. The Hospital Anxiety and Depression Scale (HADS) and the Impact of Event Scale-Revised (IES-R) were used for assessing depression and anxiety symptoms and the psychological impact of COVID-19, respectively. Multiple linear regression analyses were conducted. At the assessment, participants did not report clinically relevant depression, anxiety, and psychological pandemic-related distress symptoms. However, significant mean differences between baseline and current follow-up evaluations for both depression and anxiety were found, reflecting a decrease in symptomatology over time (p < .001). Baseline depression symptoms (β = 1.483, p = .005) significantly predicted the psychological impact of COVID-19 after 10 years. Conversely, their decrease (β = −1.640, p < .001) and living with others (β = −7.274, p = .041) significantly contributed to lower psychological distress scores. Our findings provide insight into the predisposing influence of depressive symptoms on pandemic-related psychological distress ten years later. Preventive interventions and strategies considering these factors are needed to better pre-empt the severe mental consequences of the pandemic.